The Limits of Indonesia’s Legal Framework for Electromobility - Ibrahim Nur, Asrul (Lentera Hukum, 2022)
The rise in global temperature indicates the impact of climate change, encouraging more countries to adapt and seek practical solutions. Several countries, including Indonesia, have begun to regulate electric vehicles because of the commitment to reduce carbon dioxide emissions. It simultaneously provides opportunities for developing electric vehicles to prevent more use of fossil fuels. This study aimed to discuss and explore Indonesia's trajectory to develop a legal framework for electromobility that started to be drafted in 2019. This framework has resulted in legal fissures because of the lack of regulations to promote electric vehicles against the environmental aspects, whereas it tends to focus on industrial development. Finally, this study discussed regulatory issues and predicted the future of Indonesia's electromobility legal development through the lens of sustainability. This study used normative legal research whose analysis inventoried and identified several laws and regulations on electromobility in Indonesia with particular criteria. This study showed that Indonesia's legal development of electromobility is being accomplished by autonomous and inconsistent delegated regulations with technical and non-technology aspects. Adopting a legal instrument through Presidential Regulation is insufficient to build an electromobility ecosystem that involves many sectors. In contrast, an imbalance in the regulatory framework, the three pillars of sustainability, and the economic dimension outweigh the social and environmental factors. Insofar, the regulations adopted prioritize the economic aspect, and the framework has impacted other industries, including mining and international trade, due to the need for nickel and manganese as raw materials for electric vehicle batteries.Keywords: Electromobility, Indonesia, Legal Framework, Sustainability.